1991
DOI: 10.1055/s-2007-1024653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemodynamic and Left Ventricular Responses to Increased After-Load in Healthy Males and Females

Abstract: Hemodynamic and left ventricular responses were studied echocardiographically in 20 males (31.5 +/- 4.5 yrs) and 20 females (30.4 +/- 4.3 yrs) at rest and during 3 min of isometric deadlift exercise at 30% of maximum voluntary contraction. Maximal tension exerted was significantly (P less than .001) lower in the female group (87.4 +/- 8.1 kg) compared with the male group (127.3 +/- 15 kg). Significant (P less than .001) increases in heart rate and contractility index were noted in both groups during exercise c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…These left ventricular responses were similar to those observed during isometric exercise (Bryg et al 1989;Sagiv et al 1985). During isometric exercise, it has been reported that afterload is elevated while stroke volume does not increase; rather a marked increase in heart rate has been noted as the factor for maintaining adequate cardiac output (Hossack and Bruce 1982;Sagiv et al 1991). The results for the Doppler derived indices and blood pressure response in the present study were similar to those seen during isometric exercise.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These left ventricular responses were similar to those observed during isometric exercise (Bryg et al 1989;Sagiv et al 1985). During isometric exercise, it has been reported that afterload is elevated while stroke volume does not increase; rather a marked increase in heart rate has been noted as the factor for maintaining adequate cardiac output (Hossack and Bruce 1982;Sagiv et al 1991). The results for the Doppler derived indices and blood pressure response in the present study were similar to those seen during isometric exercise.…”
Section: Discussionsupporting
confidence: 92%
“…It is well-established that maximal aerobic power (watts) is highly correlated with the mass of skeletal tissue that is active during the exercise (Fagard et al 1995). It has been found that both body mass and lean body mass tend to be lower in women than men (Sagiv et al 1991) and thus, maximal aerobic power would be expected to be lower in the average woman than in the average man as reported previously (Fagard et al 1995;Sagiv et al 1991). However, in the present study, body mass and lean body mass were similar, and because all the subjects were exercised to a level of severe fatigue, it seems that the dierences were due to gender dierences and not to lack of motivation on the part of the women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All measurements were compared to norms for young adults [13,14]. The subjects' hematological profiles are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It remains debatable whether the pressor response is due to increases in cardiac output (CO) [5][6][7][8][9], total peripheral resistance (TPR) [10][11][12][13][14] or both [15][16][17][18]. CO changes during IHG is primarily driven by an elevated heart rate (HR), whilst the stroke volume (SV) is slightly reduced due to the tachycardia and increased afterload, or even maintained following both augmented ventricular contractility [19,20] and constant or elevated preload via central blood volume mobilization [21].…”
Section: Introductionmentioning
confidence: 99%